2019
DOI: 10.1186/s13047-019-0350-1
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of the ankle brachial index: a systematic review

Abstract: Background The ankle brachial index (ABI) is widely used in clinical practice as a non-invasive method to detect the presence and severity of peripheral arterial disease (PAD). Current guidelines suggest that it should be used to monitor potential progression of PAD in affected individuals. As such, it is important that the test is reliable when used for repeated measurements, by the same or different health practitioners. This systematic review aims to examine the literature to evaluate the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 79 publications
(227 reference statements)
0
43
0
2
Order By: Relevance
“…29,30 In the present study, we found that an accurate handheld thermometer allows detecting baseline foot skin temperature with high reproducibility by avoiding factors influencing foot skin temperature levels. Regarding reliability, interrater reliability of ABI showed varied data from poor to excellent (ICC: 0.42-1.0) in the recent meta-analysis, 31 but that of our method was excellent (ICC: 0.94), which was very high. It is superior to ABI that our method has good reliability without special training.…”
Section: Discussionmentioning
confidence: 58%
“…29,30 In the present study, we found that an accurate handheld thermometer allows detecting baseline foot skin temperature with high reproducibility by avoiding factors influencing foot skin temperature levels. Regarding reliability, interrater reliability of ABI showed varied data from poor to excellent (ICC: 0.42-1.0) in the recent meta-analysis, 31 but that of our method was excellent (ICC: 0.94), which was very high. It is superior to ABI that our method has good reliability without special training.…”
Section: Discussionmentioning
confidence: 58%
“…The clinical relevance of these changes remains questionable. ABI and TBI have been described to have a heterogeneous reliability, affected by co-morbidities such as medial arterial calcification and diabetes [ 36 , 37 ]. Therefore, we consider that our results, even if statistically significant, have no clinical repercussions.…”
Section: Discussionmentioning
confidence: 99%
“…ABI has been shown to be a non-invasive, sensitive, specific, and cost-effective tool for lower limb vascular assessment and evaluating atherosclerosis in lower limbs. It represents the ratio of the ankle to brachial systolic pressure and is calculated by dividing the higher systolic pressure of the dorsalis pedis and tibialis posterior vessels at the ankle with that measured in the brachial artery in both arms [ 14 ]. An ABI below 0.9 is considered a powerful independent marker of coronary morbidity and mortality [ 15 ].…”
Section: Discussionmentioning
confidence: 99%